2020
DOI: 10.1177/0271678x20968943
|View full text |Cite
|
Sign up to set email alerts
|

A novel molecular magnetic resonance imaging agent targeting activated leukocyte cell adhesion molecule as demonstrated in mouse brain metastasis models

Abstract: Molecular magnetic resonance imaging (MRI) allows visualization of biological processes at the molecular level. Upregulation of endothelial ALCAM (activated leukocyte cell adhesion molecule) is a key element for leukocyte recruitment in neurological disease. The aim of this study, therefore, was to develop a novel molecular MRI contrast agent, by conjugating anti-ALCAM antibodies to microparticles of iron oxide (MPIO), for detection of endothelial ALCAM expression in vivo. Binding specificity of ALCAM-MPIO was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…It appears that the main source of ALCAM in brain imaging and histology analyses is likely to be endothelial cells, and normal brain tissue appears to be negative, emphasising the relatively exclusive nature of ALCAM in the cell type. The other interesting finding is that the blood-brain barrier appears to be intact as the metastatic legion had virtually no trace from the conjugate [137]. This is a very interesting finding, however, with some limitations.…”
Section: Alcam and Diagnostic And Therapeutic Considerationsmentioning
confidence: 87%
See 2 more Smart Citations
“…It appears that the main source of ALCAM in brain imaging and histology analyses is likely to be endothelial cells, and normal brain tissue appears to be negative, emphasising the relatively exclusive nature of ALCAM in the cell type. The other interesting finding is that the blood-brain barrier appears to be intact as the metastatic legion had virtually no trace from the conjugate [137]. This is a very interesting finding, however, with some limitations.…”
Section: Alcam and Diagnostic And Therapeutic Considerationsmentioning
confidence: 87%
“…Brain metastases in selenoglycoprotein fed mice had markedly reduced brain metastasis and tumour intra-and extravasation in brain vasculatures, which appears to be a result of reduction in ALCAM and PECAM1 in the mice [122]. Other work has shown that an antibody to ALCAM can recognise well endothelial cells surrounding metastatic tumours of the brain [137], indicating a cell-based targeting possibility, namely targeting tumourassociated endothelium. However, a great deal has yet to be learned here.…”
Section: Alcam As a Therapeutic Targetmentioning
confidence: 93%
See 1 more Smart Citation
“…In preclinical studies, blocking VLA-4 or ALCAM on tumour cells ( via incubation with neutralizing antibodies) resulted in a significant decrease in the number and volume of BM in comparison to the unblocked cells ( 19 ). Importantly, endothelial CAM overexpression has been observed in early BM in both preclinical studies and human tissue ( 20 , 21 ). VCAM-1, in particular, has been presented as a major biomarker of tumorigenesis in many types of cancers, further reinforcing its early biomarker status ( 22 ).…”
Section: Early Biomarkers Of Bmmentioning
confidence: 99%
“…ALCAM-MPIO induced hypointensities were seen on T2* weighted MRI in all models, while post gadolinium MRI showed that the BBB was intact. 57 …”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%